## Trending News

Promoted

### 4 Answers

Relevance

- 1 decade agoFavorite Answer
I presume the question is really "simplify", as there is no single numeric "answer" to the question; in which case; remembering the rule to perform any operation to both sides of the equation:

3x+9y=0 divide both sides by 3, =>

.

x+3y=0 Subtract 3y from both sides =>

x = -3y Divide both sides by 3 =>

y = -x/3

The function describes a straight line, through the point (0,0) with a gradient of -1/3.

- 1 decade ago
(trial and error form)

let x=-3 and y=1

3(-3) + 9(1)=0

-9 + 9=0

which makes the equation correct, so the answer is

x= 3

y=1

trial and error form is the easiest form of solving

Still have questions? Get your answers by asking now.